PERSEPSI MAHASISWA GURU GENERASI Z MENGENAI KOMPETENSI KEPRIBADIAN DALAM KONTEK MAGANG DI SEKOLAH - Bernard Wijaya; Maha Dewi Sabrina Nalle (STKIP Pesisir Selatan, 2026)
Objective: Teacher professionalism must be developed in university. However, student teachers' perceptions of professionalism vary widely. Previous research shows that teacher professionalism closely relates to how student teachers think critically and confidently in the classroom. However, it has not examined the conditions of generation Z in Indonesia. The purpose of this study is to determine the extent of the difference in perceptions of personality competencies between student teachers of generation Z and government standards in the Indonesian context, and the focus is improving the professionalism of student teachers of generation Z. The novelty of this study are the perceptions of generation Z students in Indonesia regarding personality competencies. The research subjects were 3rd-year student teachers, 5th semester, totaling eight people with diverse backgrounds. The data collection was carried out through interviews conducted by a third person. The research method is descriptive and qualitative, where data analysis uses coding. The results of the study show 1) Students have different perceptions of personality competencies. 2) Students have different perceptions of a mature teacher. 3) Students have a future desire for mature personality development, particularly in terms of maturity, being reflective, being sensitive to oneself, and being more objective in self-evaluation. These results illustrate that students' perceptions of teacher professionalism differ and tend to increase maturity and evaluate themselves objectively. This research has limitations where other competencies have not been studied and the context of student teacher practicums is homogeneous.